Variability in Trauma Case Volume in Orthopedic Surgery Residents - Blood, Travis D. (Orthop Rev (Pavia), 2017)
Orthopedic trauma surgery is a critical component of resident education. Surgical case logs obtained from the Accreditation Council of Graduate Medical Students from 2009 to 2013 for orthopedic surgery residents were examined for variability between the 90(th) and 10(th) percentiles in regards to the volume of cases performed. There was an upward trend in the mean number of cases performed by senior residents from 484.4 in 2009 to 534.5 in 2013, representing a 10.3% increase. There was a statistically significant increase in the number of cases performed for humerus/elbow, forearm/wrist, and pelvis/hip during this period (P<0.05). Although the difference between the 10(th) and 90(th) percentile case volumes narrowed over the study period, the difference between these groups remained significant in 2013 (P=0.02). In 2013, all categories of trauma cases had a greater than 2.2-fold difference between the 10(th) and 90(th) percentile of residents for numbers of trauma cases performed. Although case volume is not the sole determinant of residency education and competency, evidence suggests that case volume plays a crucial role in surgeon confidence and efficiency in performing surgery. Further studies are needed to better understand the effect of this variability seen among residents performing orthopedic trauma surgery.